2011
DOI: 10.1163/156853011x578929
|View full text |Cite
|
Sign up to set email alerts
|

Interest Groups and Pro-Animal Rights Legislation

Abstract: The American states have demonstrated varying levels of support for animal rights legislation. The activities of interest groups, including pressures from competing groups, help to explain the presence or absence of ten pro-animal regulations and laws. This article analyzes and ranks each of the fifty states with regard to ten key areas of animal protection and welfare legislation. The analysis reveals that states with a more agricultural economic base are less likely to provide protection to animals. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…But they also adapted it to their context and structure of their own social system (Rogers, 2003), not losing the essence like the ban of bullfights and other cruel practices. This diffusion mechanism was also observed by Lutz and Lutz, where the creation of animal legislation in one place favors the creation of alike legislation in another (Lutz & Lutz, 2011).…”
Section: Policy Diffusion Outcomessupporting
confidence: 69%
See 2 more Smart Citations
“…But they also adapted it to their context and structure of their own social system (Rogers, 2003), not losing the essence like the ban of bullfights and other cruel practices. This diffusion mechanism was also observed by Lutz and Lutz, where the creation of animal legislation in one place favors the creation of alike legislation in another (Lutz & Lutz, 2011).…”
Section: Policy Diffusion Outcomessupporting
confidence: 69%
“…The soft coercion mechanism was followed by geographic closeness or clustering given that spatial proximity allows for both easier interaction and influence (Strang & Soule, 1998) between governments. It was also observed by Lutz and Lutz that the creation of animal legislation in one place favors the creation of alike legislation in another (Lutz & Lutz, 2011).…”
Section: Policy Diffusion Outcomesmentioning
confidence: 84%
See 1 more Smart Citation
“…While much of the debate around political culture has been in terms of its measurement (Johnson, 1976;Lieske, 1993Lieske, , 2010Lieske, , 2012Sharkansky, 1969), there is ample evidence to suggest that Elazar's original conception does play a role in understanding state politics. Scholars have found that this formulation, or others that have been created that are related to it, helps in predicting numerous political policies and outcomes (for a small sample, see Boeckelman, 1991;Koven & Mausloff, 2002;Lutz & Lutz, 2011;Mead, 2004;Miller, 1991).…”
Section: Political Culture and Public Opinionmentioning
confidence: 99%
“…Still, Elazar's work has influenced a broad range of scholarship. For example, recent research has found that political culture affects such diverse policy areas as state budgeting (Koven & Mausolff, 2002) and pro-animal rights legislation (Lutz & Lutz, 2011).…”
mentioning
confidence: 99%